Die Schweiz im KSZE-Prozeß 1972-1983 : Einfluß durch Neutralität - Rosin, Philip (2014)
Switzerland was not content to stay on the sidelines of the CSCE (Conference on Security and Cooperation in Europe) negotiations. Particularly in the area of human rights policies and by applying its talent for successful mediation between East and West, Switzerland achieved great recognition, as Philip Rosin’s thoroughly researched and methodologically persuasive study clearly reveals.